Bilateral temporomandibular joint ankylosis related to trauma (2013)
Temporomandibular joint ankylosis may be defined as thepartial or total fusion of the articular surfaces with bonyor fibrous tissue. It has been related with trauma events tothe condylar process, which may derive in lack of developmentof the mandible, causing facial asymmetries and compromisingnormal function. Numerous techniques havebeen described for treatment, within which include theaggressive excision of the ankylotic mass, with or withoutthe employment of interposition material and the use ofautologous graft for reconstruction. The choice of treatmentbecomes a challenge to the surgeon, because of thehigh incidence of recurrence. We present a case of a malepatient with history of trauma, under the diagnosis of bilateraltemporomandibular joint ankylosis; which was treatedthrough arthroplasty, placement of interposition materialand autologous graft of coronoid process.